Cjelovita naučna studija o nastanku i razvoju ljudskih prava / The Complete Study of HUman Rights Origin and Development - Pejanović, Mirko (Pregled: časopis za društvena pitanja / Periodical for social issues, 2017)
This text is the review of a book The Right of Association, Political Parties and Non-Governmental Organizations in the Contemporary Legal and Political System, Comparative and International Law by Dr. Rebeka Kotlo, University Press, Sarajevo, 2017.